PENINGKATAN HASIL PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE TGTDI KELAS IV SD NEGERI 12 KOTO SANI KECAMATAN X KOTO SINGKARAK SOLOK - KHAIRAWATI, YENI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The puprpose of this research was to descri the improvement of the students’ learning achiement in civic by using TGT cooperative model in grade IV of SD Negeri 12 Koto Sani .To conduct the researt, botd qualitative approaches were applied. The subjek of the research was 20 Student in grade IV of SD Negeri 12 Koto Sani.Based on the results of the research, in was figured out that from cycle I to cycle II, the student’ learning achiement improved from 70 to 86. Thus, the use of TGT cooperative model could increasw the students’ learning achivement in civics in grade IV of SD Negeri 12 Koto Sani. Key Terms  : Civics Learning Achievement, TGT Cooperative Model